Effect of Giving Api-Api (Avicennia marina ) Mangrove Leaf Solution In Artificial Feed On The Immunity Response and Growth of Vannamei Shrimp (Litopenaeus vannamei) - Linayati, Linayati; Rattanavichai, Wutti; Mardiana, Tri Yusufi; Nugroho, Leonardus Bayu; Yahya, Muhammad Zulkham (Department of Aquaculture, 2024)
The purpose of this study was .to determine the effect of giving Avicennia marina mangrove leaf solution on artificial feed to increase the immune response and growth of vannamei shrimp. The parameters observed in this study were the enhancement of PA value (Phagocytosis Activity), ADG (Average Daily Growth), FCR (Feed Conversion Ratio), and EPP (Efficiency of Feed Utilization). The vannamei shrimp used was PL-20 fry with the weight of 1,09 – 1,13 gâ‹…head-1 and density 1 shrimp L-1. The method used in this study was an experimental method in the laboratory, with a completely randomized design (CRD) with 4 treatments and 3 replications. This research was conducted by adding Avicennia marina mangrove leaf solution to the feed, with treatments of A (control), B (125